Planning Regulation, Property Protection, and Regulatory Takings in the Greek Planning Law - Georgia Giannakourou (Washington University Global Studies Law Review, 2006)
The next section of the Article will address the question of takings with regard to the provisions of the Greek Constitution. It will attempt to formulate a typology of potential regulatory takings in Greece, based on the types of injurious planning decisions that have emerged in recent practice. Afterward, the paper will examine the statutory regimes for takings compensation as well as the compensation instruments. The last section of the paper will present critical remarks on the current state of Greek planning law, contemporary practices, and the prospect of the takings issue in Greece.
Keywords: Regulatory takings